2012
DOI: 10.1186/bcr3210
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy contrast-enhanced digital mammography: initial clinical results of a multireader, multicase study

Abstract: IntroductionThe purpose of this study was to compare the diagnostic accuracy of dual-energy contrast-enhanced digital mammography (CEDM) as an adjunct to mammography (MX) ± ultrasonography (US) with the diagnostic accuracy of MX ± US alone.MethodsOne hundred ten consenting women with 148 breast lesions (84 malignant, 64 benign) underwent two-view dual-energy CEDM in addition to MX and US using a specially modified digital mammography system (Senographe DS, GE Healthcare). Reference standard was histology for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 29 publications
(38 reference statements)
8
151
0
5
Order By: Relevance
“…Dromain, Thibault, and Diekmann, et al [8] from France have published an impressive paper on the procedure. They presented their initial clinical results of a multireader, multicase study.…”
Section: Discussionmentioning
confidence: 99%
“…Dromain, Thibault, and Diekmann, et al [8] from France have published an impressive paper on the procedure. They presented their initial clinical results of a multireader, multicase study.…”
Section: Discussionmentioning
confidence: 99%
“…DE X-ray breast imaging has been shown to aid visualization of lesions that are otherwise mammographically occult as well as to provide functional blood flow information consistent with MRIthe current gold standard in functional breast imaging. [1][2][3]7,8 This has led to the development of several DE imaging systems by Hologic® (Bedford, MA), General Electric (GE; Fairfield, CT) and Royal Philips (Amsterdam, Netherlands). 7,9,10 Currently, CEDE breast imaging is performed with an iodinated contrast agent.…”
Section: Contrast-enhanced (Ce) Dual-energy (De) X-ray Breastmentioning
confidence: 99%
“…The raw pixel values were measured in a region of interest (3.5 3 3.5 mm) after the system-specific flat-fielding algorithm was applied. W was then calculated using Equation (3). Multiple regions of interest were used to determine the error in the calculation of W.…”
Section: Validating the Simulation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, CEDM is not used as a screening method due to iodine injection which causes discomfort of patients. However, it has been reported that CEDM can be an alternative screening method to breast MRI for a high-risk group [4,5]. Thus, the method to improve detectability of cancer by iodine injection seems to have the potential to be more widely used.…”
Section: Introductionmentioning
confidence: 99%